Visiting the secondary social studies curriculum in perilous times - Tyrone Ogaro Gil Jr (Journal of Social Studies (JSS), 2022)
In such perilous times and unabated marginalization, it is pivotal to pay a visit to the secondary social studies curriculum. This article will decipher the status of the implementation and academic location of secondary social studies in the emergency curriculum (MELCs). Through a careful examination of the Most Essential Learning Competencies (MELCs), developed self-learning modules (SLM), and field notes collected from the curriculum gatekeepers (secondary social studies teachers), the researcher was able to generate exhaustive and perplexing findings in remote teaching-learning of social studies.